2014
DOI: 10.1039/c3sc53315h
|View full text |Cite
|
Sign up to set email alerts
|

Beam pen lithography as a new tool for spatially controlled photochemistry, and its utilization in the synthesis of multivalent glycan arrays

Abstract: Herein, we describe how cantilever-free scanning probes can be used to deposit precursor material and subsequently irradiate the precursor to initiate polymerization, resulting in a 3D lithographic method wherein the position, height and diameter of each feature can be tuned independently. Specifically, acrylate and methacrylate monomers were patterned onto thiol terminated glass and subsequently exposed to UV light produced brush polymers by a photoinduced radical acrylate polymerization reaction. Here, we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(102 citation statements)
references
References 78 publications
3
98
1
Order By: Relevance
“…Most recently, Braunschweig et al employed a new approach by combining polymer pen lithiography (PPL) and beam pen lithiography (BPL) with acrylate or methacrylate photo polymerization chemistry to generate arrays of brush polymers with side chain functionalized with fluorophores or glycans [40]. They patterned acrylate and methacrylate monomers (α-mannose and α-glucoside) onto thiol coated glass slides and exposed these glass slides to UV light that produced brush polymers by a photoinduced radical acrylate polymerization reaction.…”
Section: Glycopolymer-based Glycan Microarraymentioning
confidence: 98%
See 1 more Smart Citation
“…Most recently, Braunschweig et al employed a new approach by combining polymer pen lithiography (PPL) and beam pen lithiography (BPL) with acrylate or methacrylate photo polymerization chemistry to generate arrays of brush polymers with side chain functionalized with fluorophores or glycans [40]. They patterned acrylate and methacrylate monomers (α-mannose and α-glucoside) onto thiol coated glass slides and exposed these glass slides to UV light that produced brush polymers by a photoinduced radical acrylate polymerization reaction.…”
Section: Glycopolymer-based Glycan Microarraymentioning
confidence: 98%
“…[11,13,33] Fig. 4 Glycopolymer-based glycoarray: a duel end functionalized mucin like glycopolymer with alkyne on one end and Texas Red dye on the other end [24], b mucin like glycopolymer presentation that mimics native mucin [40], c biotin end functionalized glycopolymer immobilized glass slide [26], d glycopolymer formation at different illumination times [41], e O-cyanate end functionalized glycopolymer immobilized on amine functionalized glass slide [27], f O-cyanate chain-end functionalized glycopolymer pre-complexed and immobilized with boronic acid ligands of different sizes [28]. Modified from Ref.…”
Section: Glycopolymer-based Glycan Microarraymentioning
confidence: 99%
“…In a later study [116], their interaction with blood was also examined and it was found that the nature of the sugar group (Glc, Man, or Gal) has an effect on the amount and type of plasma proteins being adsorbed, with glucose-functionalized brushes leading to the lowest adsorption. Bian [117] et al reported an example of glycan arrays decorated with Concanavalin A, creating glycan-functionalized polymer brushes with pendant carbohydrate side groups by the thiol-acrylate photopolymerization. The results of this study have demonstrated that polymer brushes are better polymer scaffolds than their counterpart SAM decorated with α-mannosides and α-glucosides.…”
Section: Non-covalent Protein Immobilizationmentioning
confidence: 99%
“…Inspired by the concept of DNA and protein biosensors, carbohydrate-functionalized biosensors, which are composed of carbohydrate attached to a solid surface, have recently been developed as reliable and efficient tools for the assay of biological analytes (Pussak et al, 2013;Shin et al, 2005;Martin et al, 2013). This technology not only facilitates fast and sensitive analysis of a large number of biomolecules, but also effectively mimics the presentation of glycans on living cell surface to exhibit multivalent interactions with receptors (Bian et al, 2014;Mader et al, 2012). Regarding the construction of the carbohydratefunctionalized biosensor, the efficient immobilization of carbohydrates is an important factor because carbohydrates do not have functional groups (Yamada et al, 2013).…”
Section: Introductionmentioning
confidence: 99%